HUMAN EXPOSURETQ POLLUTANTS Part-I.Blood Lead and Cadmium levels in a Sample of Population of karachi (Biological Sciences - PJSIR, 2022)
A study was carried out to see the blood lead and cadmium levels in fifty employees working at PCSIR LaboratoriesComplex, Karachi. These employees belonged to various socio-economic groups and had their residences in differentareas of Karachi. Sixty two percent staff had blood lead level between 100-200 IlgJL. The highest blood lead level (>4qOIlgJL) was found in volunteers working as garage staff. No significant difference was found between the·blood lead Ie~elsof volunteers belonging to different socio-economic and age groups. Only 8% or'the staff had blood lead Ie~els'below100 IlgJL. Lead in the dust collected from the residences of the volunteers was also estimated for lead and correlated withblood lead levels. Blood cadmium levels were also estimated. These were found to be higher in smokers and tobaccochewers. A definite correlation was observed between blood cadmium levels and smoking habits.